Influence of colored polyvinyl chloride films as light filters on the growth of iceberg lettuce (Lactuca sativa var. capitata Linnaeus) - Fritz Gerard Javier; Ma. Grace Curay (Annals of Tropical Research, 2025)
The two components of light – light quality and light intensity – significantly affect plant photosynthesis as well as the morphological, physiological, and biochemical parameters of plants. The response of plants to different spectral radiations and intensities differs in various species and depends on growing conditions. Four set-ups were constructed for each film color to test its influence on the growth of iceberg lettuce (Lactuca sativa var. capitata L.). A drip irrigation system passed through the four set-ups and supplied water throughout the duration of the study. Temperature and Humidity sensors were also installed to monitor maximum and minimum temperature and humidity values. Three replications were made following the Completely Randomized Design (CRD). Each replication obtained data regarding chlorophyll a and b, light intensity, fresh weight, plant height and number of lettuce leaves. The analysis reveals significant difference between set-ups suggesting how film color influences the growth of iceberg lettuce in terms of light intensity received, lettuce height and fresh weight (Transparent>Purple>Blue>Red), while there is not enough evidence to support that film color influences the number of leaves. In addition, results of the laboratory analysis also revealed that Transparent chlorophyll a and b while blue light exhibited higher chlorophyll b than red light and the latter having higher chlorophyll a than blue light. The main objective of this study is to observe the influence of colored polyvinyl chloride films as light filters on the growth of iceberg lettuce (Lactuca sativa var. capitata Linnaeus).